SANTRI DAN MULTIKULTURALISME - Roihanah, Roihanah; Husna, Ma’rifatul; Maulida, Vina (LP3M IAI Al-Qolam, 2017)
Sambas conflict in 1997 and 1999 caused big number of refugees, mainly Madureses, which spread in various regions. Many young refugees were sheltered at Islamic boarding schools (pondok pesantren), especially in East Java. They usually got special treatment, from financial dispensation to psychological assistance. One pondok pesantren accommodating the Victims of Sambas conflict was Raudlatul Ulum 1 Ganjaran Gondanglegi Malang. Although it did not have particular program to handle those young victims, a number conflict victims were found. The research problems are formulated as follows: (1) how is the Sambas conflict victimsÃ¢â¬â¢ perception on multiculturalism at Islamic boarding School Raudlatul Ulum 1; (2) what is the role of the boarding school in the formation of their perception on multiculturalism? It is a field research with qualitative approach. This research resulted that the conflict which the victims had experienced in Sambas had provided deep trauma, especially psychologically one. Their mentality and perceptions are also affected significantly, especially shortly after the conflict. This is noticed from their fear of meeting with people from different ethnicity, especially Dayak and Melayu. But over time, the trauma turned into an understanding that the conflicts occurred because of economic interest or because of political engineering based on the interests of the rulers. One of the factors that shape their perception of this conflict is pondok pesantren. Its environment and the education system significantly affected their perception. Pondok pesantren inhabited by the students with quite vast of race, ethnicity or language, thereby building tolerance between them, while its education system could build the character of leaders who are ready to protect the society with all its diversity.